ID 411 – Diffuse hyperpathia in a case of Wernicke's-like encephalopathy. Issue 3 (March 2016) - Addis, A.; Sechi, E.; Rassu, A.L.; Piredda, R.; Sechi, G.P.
Abstract : Objective: Bilateral thalamic lesion is highly suggestive of thiamine deficiency. Thalamic hyperpathia has never been reported as a feature of thiamine-related disorders. We propose a case of Wernicke's-like encephalopathy manifesting as intolerable touch-evoked pain resembling thalamic hyperpathia. Methods: A 22-year-old female was admitted for reduced level of consciousness after four days history of fever complicated with drowsiness and ataxia. A previous evaluation by the EMS had been obstructed by the fact that she felt an intense pain whenever touched, even lightly. Brain-MRI showed T2 hyperintensity of bilateral thalami, heads of caudate nuclei and periaqueductal region. Laboratory investigation excluded infectious-autoimmune etiology. Despite serum levels within normal range, high dose thiamine was administered with prompt improvement of symptoms supporting the suspicion of a genetic origin of the disorder. Results: Gene sequencing disclosed a novel mutation of THTR-2 gene encoding for human thiamine transporter type 2. Conclusions: The patient manifested a diffuse, touch-evoked, intense pain, not restricted to any radicular/peripheral nerve territory, as occurs in typical thalamic hyperpathia. This symptom could be related to the thalamic lesions documented on MRI. Both the painful condition and the radiological findings resolved after thiamine supplementation. Key message: Thiamine-related thalamic lesions could be a cause of thalamic hyperpathia.